2011
DOI: 10.1016/j.gep.2010.12.003
|View full text |Cite
|
Sign up to set email alerts
|

Tissue specific characterisation of Lim-kinase 1 expression during mouse embryogenesis

Abstract: The Lim-kinase (LIMK) proteins are important for the regulation of the actin cytoskeleton, in particular the control of actin nucleation and depolymerisation via regulation of cofilin, and hence may control a large number of processes during development, including cell tensegrity, migration, cell cycling, and axon guidance. LIMK1/LIMK2 knockouts disrupt spinal cord morphogenesis and synapse formation but other tissues and developmental processes that require LIMK are yet to be fully determined. To identify tis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 36 publications
0
8
0
Order By: Relevance
“…Importantly, the mechanistic basis for the pathway downstream of Rho and Rho kinases resides in a previously unidentified process, the interaction of LIMK1/2 with fascin-1. Both of the LIMK isoforms are expressed in many tissues, although specificity of expression patterns and subcellular localizations has been described [ 37 , 45 , 46 ]. In this study, we identified the interaction of fascin-1 with active LIMK1/2 in SW480 cells by biochemical pull-down from cell extracts and by FRET/FLIM in intact, migrating cells.…”
Section: Discussionmentioning
confidence: 99%
“…Importantly, the mechanistic basis for the pathway downstream of Rho and Rho kinases resides in a previously unidentified process, the interaction of LIMK1/2 with fascin-1. Both of the LIMK isoforms are expressed in many tissues, although specificity of expression patterns and subcellular localizations has been described [ 37 , 45 , 46 ]. In this study, we identified the interaction of fascin-1 with active LIMK1/2 in SW480 cells by biochemical pull-down from cell extracts and by FRET/FLIM in intact, migrating cells.…”
Section: Discussionmentioning
confidence: 99%
“…LIMK1 and LIMK2 are most abundant in neural tissue, but are also present in numerous tissues including in the Z-discs of the developing heart (384, 501). LIMK1 phosphorylates cofilin-1 at serine 3, which inhibits cofilin-1’s function as an actin-severing protein (24).…”
Section: Sarcomere—the Basic Contractile Unit Of Striated Musclementioning
confidence: 99%
“…They regulate actin cytoskeletal assembly via the actin‐binding protein, cofilin, of which only the dephosphorylated form is active 70. LIMK1 itself is phosphorylated by Rho‐GTPases which in turn inactivate cofilin, thereby blocking its action on actin filaments and inhibiting de‐branching 71. This inhibition normally acts through the competitive binding of cofilin and the Arp2/3 complex to actin filaments.…”
Section: Sources Of Informationmentioning
confidence: 99%